2015
DOI: 10.1039/c5cc05195a
|View full text |Cite
|
Sign up to set email alerts
|

The in situ synthesis of Ag/amino acid biopolymer hydrogels as mouldable wound dressings

Abstract: This manuscript introduces a one-pot fabrication procedure for the preparation of supramolecular hybrid hydrogels from low-cost commercially available natural products through a "green" strategy. In particular, the hybrid hydrogels, which are developed with Fmoc-Glu-OMe, silver nanoparticles and chitosan, exhibit outstanding antibacterial properties and can be regarded as excellent mouldable wound healing biomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…Metal cations can be adsorbed by chelation on amino groups of CS due to the free electron doublet on nitrogen, and hydroxyl groups (especially in the C-3 position) may also contribute to sorption28. While most researchers focused directly on the applications of complexes between CS and metal ions, like decontamination of effluents29, catalysis industry30, advanced composite soft materials3132, and noble metals reclamation33, few attention was paid on the design of novel hydrogel materials with hierarchical structure taking advantage of the complexes. In addition to the interaction of metal ions and CS on molecular level, it has been reported that the introduction of metal ions can influence the structure of in-situ prepared CS hydrogel3435.…”
mentioning
confidence: 99%
“…Metal cations can be adsorbed by chelation on amino groups of CS due to the free electron doublet on nitrogen, and hydroxyl groups (especially in the C-3 position) may also contribute to sorption28. While most researchers focused directly on the applications of complexes between CS and metal ions, like decontamination of effluents29, catalysis industry30, advanced composite soft materials3132, and noble metals reclamation33, few attention was paid on the design of novel hydrogel materials with hierarchical structure taking advantage of the complexes. In addition to the interaction of metal ions and CS on molecular level, it has been reported that the introduction of metal ions can influence the structure of in-situ prepared CS hydrogel3435.…”
mentioning
confidence: 99%
“…Metallogels, especially metallohydrogels containing Au nanoparticles (AuNPs) and Ag nanoparticles (AgNPs) are wildly applied in biological applications such as antibacterial materials, anticancer therapy, cell culture, and tissue repairing . Due to their localized surface plasmon resonance (LSPR), noble‐metal nanoparticles absorb light at certain wavelengths and they have enhanced absorption ratio in comparing with conventional photoabsorbing dyes .…”
Section: Fundamental Applications Of Metallogelsmentioning
confidence: 99%
“…Fmoc‐Val‐Asp‐OH and Fmoc‐ l ‐phenylalanine formed AgNP gels after exposure to sunlight. Zhang et al also demonstrated the ability of natural materials to act as a matrix to bear the sunlight‐reduced AgNPs.…”
Section: Fundamental Applications Of Metallogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of AgNPs into hydrogels can endow hydrogels with enhanced performance and new properties20. Furthermore, the three-dimensional hydrogel networks can facilitate the dispersion and stabilization of AgNPs2122. Abdel-Halim and his coworker adopted guar gum together with poly(acrylic acid) to prepare hydrogels which were used as a matrix for AgNPs23.…”
mentioning
confidence: 99%